2011
DOI: 10.1007/s00411-011-0380-y
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity of diagnostic and therapeutical doses of radiopharmaceutical iodine-131 in Wistar rats

Abstract: Iodine-131 ((131)I) is a radioisotope used for the diagnosis and treatment of thyroidal disorders such as hyperthyroidism and cancer. During its decay, (131)I emits beta particles and gamma rays; its physical half-life is 8 days, and it is accumulated preferentially in the thyroid tissue. This study aimed to evaluate the cytotoxicity and mutagenicity of diagnostic and therapeutic doses of (131)I using bone marrow cells of rats treated in vivo in a test system with a single dose by gavage. Concentrations of 5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…This mixture of nutrients may interact with the DNA and protect it from oxidative stress. In this sense, Blumenthal et al (2000) also reported that the combination of vitamins E, C, and A, when administered to mice for 14 days (3 days before and 11 days after radiation exposure), reduced the toxic effect of radioimmunotherapy with 400 μCi [ Aside from this, significant decreases in NDI after simultaneous treatment with acerola or beta-carotene (Table 3) could be explained by the fact high NDI observed after treatment with 10 μCi [ 131 I] may have resulted from the cells attempt to rapidly divide in response to damage and quickly replace the damaged cells, as was previously described by Düsman et al (2011). Thus, acerola and beta-carotene, when administered with [ 131 I], may have reduced cell damage and decreased the NDI.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This mixture of nutrients may interact with the DNA and protect it from oxidative stress. In this sense, Blumenthal et al (2000) also reported that the combination of vitamins E, C, and A, when administered to mice for 14 days (3 days before and 11 days after radiation exposure), reduced the toxic effect of radioimmunotherapy with 400 μCi [ Aside from this, significant decreases in NDI after simultaneous treatment with acerola or beta-carotene (Table 3) could be explained by the fact high NDI observed after treatment with 10 μCi [ 131 I] may have resulted from the cells attempt to rapidly divide in response to damage and quickly replace the damaged cells, as was previously described by Düsman et al (2011). Thus, acerola and beta-carotene, when administered with [ 131 I], may have reduced cell damage and decreased the NDI.…”
Section: Discussionmentioning
confidence: 65%
“…Ionizing radiation also acts directly on nuclear DNA and may result in single-or double-strand breaks (Calegaro, 2007). Previous studies assessed the impact of various doses of radioiodine in several systems and indicated that isotope exposure increases the frequency of chromosomal aberrations (Puerto et al, 2000;da Silva et al, 2008;Düsman et al, 2011) and micronuclei (MN) (Watanabe et al, 2004;Joseph et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, the same reduction in exposure rate (82.2%) in 24 h was observed in all treatments. Regarding the elimination rate, which was measured every 4 h, most treatments presented an increase at 8 h, a decrease at 12 h, and an increase at 24 h. Düsman et al (2011). Treatments: SIM = simultaneous; PRE = pre-treatment; POST = post-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration used was 25 μCi or 0.925 MBq/100 g body weight (bw), which corresponds to the concentration that is used in the treatment of hyperthyroidism in humans and that caused a greater number of chromosomal changes in Wistar rat bone marrow cells (Düsman et al, 2011).…”
Section: Treatment Solutionmentioning
confidence: 99%
“…Several studies have confirmed the mutagenic activity of different doses of 131I based on evidence from the induction of micronuclei [2,3] and the presence of chromosomal aberrations [4,5]. …”
Section: Introductionmentioning
confidence: 99%